Shannon's Random-Cipher Result and the Generalized R-Norm Entropy of Type β - Satish Kumar; Arun Choudhary (International Journal of Mathematics and Mathematical Sciences)
Using the Fano inequality for the generalized R-norm entropy and Bayess probability of error, a generalized random-cipher result is proved by taking into account the generalized R-norm entropy of type β.